The Contractual Rights of International Civil Servants: Administrative Tribunals of the United Nations and International Labour Organization Perspective - Uddin, Kamal; Uddin, Siraj (Mediterranean Journal of Social Sciences, 2012)
International Organizations are acting within the parameters provided by the rules of procedure of the organizationand terms of their contract of employment. The International Labour Organization Administrative Tribunal (ILOAT), was createdas a judicial system for international civil servants. The United Nations Administrative Tribunal (UNAT) was established as anindependent organ competent to hear and pass judgments upon application alleging non-observance of contracts or terms ofemployment by staff members of the UN Secretariat. The two most important administrative tribunals that grant remedies toaggrieved staff of an international organization that have accepted their jurisdiction. The ILOAT and UNAT has graduallyconsolidated the idea that international organizations are under a human rights obligation to provide access to staff disputesettlement mechanisms.